Winter temperatures of southern China reconstructed from phenological cold/warm events recorded in historical documents over the past 500 years. (20th June 2018) - Zheng, Jingyun; Liu, Yang; Hao, Zhixin; Zhang, Xuezhen; Ma, Xiang; Liu, Haolong; Ge, Quansheng
Abstract: We reconstructed a 500-year long winter (November to February) temperature series with a yearly resolution in southern China. The series is based on six types of proxies extracted from historical documents, including the southern limits of frost disaster, freezing disaster and snow, along with snowfall days and the first/last frost disaster dates. In the reconstruction, linear regression models are established among each proxy and regional winter temperature. Variance matching, minimum selection, and envelope analysis methods are performed to eliminate non-homogeneous effects because of different proxy types, missing data, and the changing amount of records. Compared with the average temperatures during 1851–1950, the reconstruction shows that southern China experienced a cold period in the first 40 years of the sixteenth century with an average of −0.40 °C with frequent extremes. An upturning occurred during the 1540s to mid-1560s, followed by a stable phase until the 1620s. Then the temperature started to fall from the 1630s and reached its lowest in 1660, where it dropped to −2.01 °C. Moreover, the mean value was −0.49 °C between the years 1648–1697, which was the coldest 50 years over the last five centuries. The temperatures during the eighteenth century to the middle of the twentieth century was characterized by annual to decadal fluctuations, with two moderately warm intervals in the 1770s and 1840s–1850s, as well as three moderately cold intervals in 1790s, 1830s, and 1870s to the mid-1890s. Over the recent century, the warming rate since 1901 was 0.56 °C/100a, whereas the temperature reached 0.32 °C/10a after 1979. The hottest five years during the last five centuries all occurred after 1990.